Предмет: Алгебра,
автор: salagina03
Упростите выражение:
1) (a-2)(a-1)-a(a+1);
2) (b-5)(b+10)+(b+6)(b-8);
3) (2c+3)(3c+2)-(2c+7)(2c-7);
4) (3d+5)(5d-1)-(6d-3)(2-8d).
Ответы
Автор ответа:
0
1.а-2+а-1-а-1=2a-4
2.b-5+b+10+b+6+b-8=4b+3
3.2c+3+3c+2-2c-7+2c-7=6c-9
4.3d+5+5d-1-6d+3+2-8d=-6d+9
2.b-5+b+10+b+6+b-8=4b+3
3.2c+3+3c+2-2c-7+2c-7=6c-9
4.3d+5+5d-1-6d+3+2-8d=-6d+9
Автор ответа:
0
Вроде бы так
Похожие вопросы
Предмет: Биология,
автор: olgabogrinceva78
Предмет: Русский язык,
автор: danilabubakirov65084
Предмет: История,
автор: samsung77767679090
Предмет: Математика,
автор: enotsamurai